THE RELATIONSHIP BETWEEN INTENSITY OF PLAYING ONLINE GAMES AND ACADEMIC BOREDOM TO THE LEVEL OF AGGRESSIVENESS IN STUDENTS OF SMK X IN MOJOKERTO CITY - Imelda Nova Amalia; Ghozali Rusyid Affandi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to find out the relationship between academic boredom and the intensity of playing online games on the level of aggressiveness in vocational students. Method: In this study, researchers used a group of research subjects from a population, namely students and female students of class XI SMK X in Mojokerto City. While the number of samples in this study amounted to 5% of the total population, namely 221 students. In this study, simple random sampling technique was used as the sampling technique. Simple random sampling means giving the same opportunity to each member of the population used to become a research sample. This research is quantitative research, which is a quantitative non-experiment with a correlational approach. The data collection method used is a viewing behavior scale and an aggressive behavior scale with a Likert-shaped scale model. The data analysis technique used in this study is multiple correlation. All data analysis calculations were carried out using the SPSS application. Result: The results of the analysis show a positive and significant relationship between academic boredom and the intensity of playing online games with the level of aggressive behavior in vocational students, suggesting that higher levels of boredom and frequent gaming are associated with increased aggression. Novelty: In previous research conducted by Nabila & Sugandi, the relationship between the intensity of watching violent shows and the level of aggressive behavior was studied in adolescent targets. Therefore, in this study, researchers want to examine these two variables with a more specific target, namely vocational students. In addition, the variable of aggressiveness behavior has never been studied with the variable of academic boredom.